A review of lexical retrieval intervention in primary progressive aphasia and Alzheimer's disease: mechanisms of change, generalisation, and cognition. Issue 11 (2nd November 2018) - Beales, Ashleigh; Whitworth, Anne; Cartwright, Jade
ABSTRACT: Background : While significant benefits of lexical retrieval intervention are evident within the primary progressive aphasia (PPA) and Alzheimer's disease (AD) literature, an understanding of the mechanisms that underlie change is limited. Change mechanisms have been explored in the post-stroke aphasia literature and offer insight into how change occurs through interventions with progressive language disorders. Exploration of change mechanisms may progress our understanding as to how and why generalisation is likely, or not, to occur, as well as gain insight into the non-linguistic cognitive functions that may play a role. Aims : This review of the literature aimed to (1) map the mechanisms of change that have been proposed or hypothesised within the PPA and AD lexical retrieval intervention literature to a theoretical framework based on a framework of motor recovery following stroke and accounts of change mechanisms within the post-stroke aphasia literature and explore whether particular mechanisms of change were associated with more effective outcomes; (2) determine whether particular mechanisms of change were associated with within- and across-level linguistic generalisation, and (3) investigate the role of non-linguistic cognitive functions in the lexical retrieval intervention studies reviewed here. Main Contribution : A search of Medline, PsycINFO, and CINAHL identified 37 papers published between 1982 and April 2016 that reported lexical retrieval intervention in people with PPA or AD, categorised here according to whether the proposed change mechanism was stimulation (12 studies), relearning (21 studies), reorganisation (three studies), or cognitive-relay (two studies). Significant treatment gains, predominantly based on linguistic performance measures, were reported for both diagnostic groups in association with the proposed mechanisms of stimulation and relearning. Significant treatment gains were also reported for people with PPA in association with reorganisation and cognitive-relay mechanisms; these mechanisms were only employed in PPA studies. Varying outcomes for linguistic generalisation were reported in 26 PPA and six AD studies. Nineteen studies incorporated non-linguistic cognitive functions in intervention; these were limited to autobiographical memory (17 studies), episodic memory (three studies), or both (one study). Conclusion : This review highlights that individuals with PPA and AD benefit from lexical retrieval intervention, irrespective of the mechanism of change, and that linguistic generalisation was reported in studies proposing different change mechanisms. Insufficient exploration of the role of non-linguistic cognitive functions was highlighted with respect to assessment, planning intervention, and interpreting intervention outcomes. Recommendations are made, with a view to heightening our ability to interpret intervention outcomes.